2015
DOI: 10.1016/j.bbrep.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The intronic region of Fbxl12 functions as an alternative promoter regulated by UV irradiation

Abstract: The ubiquitin ligases, SCF complexes, consist of Cul1, Skp1, Rbx1 and the substrate recognition components F-box proteins. Previous studies have reported that one of these F-box proteins, Fbl12, which is produced by Fbxl12 gene, regulates both cell cycle and differentiation. In this paper, we show that the intronic region of Fbxl12 gene acts as an alternative promoter and induces expression of a short form of Fbl12 that lacks F-box domain (Fbl12ΔF). We also found that UV irradiation increases Fbl12ΔF mRNA in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Recently, we reported that UV irradiation induces Fbl12⌬F transcription via the alternative promoter, leading to an involvement of Fbl12 regulation (49). Since overexpression of Fbl12⌬F does not affect the cellular proliferation, it is possible that Fbl12-related pathways are linked to UV-induced DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that UV irradiation induces Fbl12⌬F transcription via the alternative promoter, leading to an involvement of Fbl12 regulation (49). Since overexpression of Fbl12⌬F does not affect the cellular proliferation, it is possible that Fbl12-related pathways are linked to UV-induced DNA damage response.…”
Section: Discussionmentioning
confidence: 99%